2019
DOI: 10.5483/bmbrep.2019.52.7.188
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of TTYH2 is attenuated by direct interaction with β-COP

Abstract: TTYH2 is a calcium-activated, inwardly rectifying anion channel that has been shown to be related to renal cancer and colon cancer. Based on the topological prediction, TTYH2 protein has five transmembrane domains with the extracellular N-terminus and the cytoplasmic C-terminus. In the present study, we identified a vesicle transport protein, β-COP, as a novel specific binding partner of TTYH2 by yeast two-hybrid screening using a human brain cDNA library with the C-terminal region of TTYH2 (TTYH2-C) as a bait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Expression of both isoforms may be important to respond to salt stress, probably to support the trafficking of ion channels or transporters. Indeed, β-COP protein has been shown to regulate the surface expression of several ion channels in mammalian cells (Ryu et al, 2019). In fact, disorders in trafficking of plasma membrane and vacuole Na + /H + antiporters in Arabidopsis may cause hypersensitivity to salt stress (Hamaji et al, 2009;Kim and Bassham, 2011;Kim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of both isoforms may be important to respond to salt stress, probably to support the trafficking of ion channels or transporters. Indeed, β-COP protein has been shown to regulate the surface expression of several ion channels in mammalian cells (Ryu et al, 2019). In fact, disorders in trafficking of plasma membrane and vacuole Na + /H + antiporters in Arabidopsis may cause hypersensitivity to salt stress (Hamaji et al, 2009;Kim and Bassham, 2011;Kim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the functions and surface expression of ion channels are regulated by protein–protein interactions [26,27]. Interestingly, recent studies showed that TTYH1 can regulate Notch signaling in neural stem cells via protein–protein interaction with Rer1 (retention in endoplasmic reticulum sorting receptor 1), and surface expression of TTYH2 is suppressed by protein–protein interactions with β-COP [13,28]. In addition, the cellular level of TTYH2 is regulated by Nedd4-2–mediated ubiquitination [29].…”
Section: Discussionmentioning
confidence: 99%
“…Short hairpin shRNA (shRNA) vectors for human LRRC8A, TTYH1, and TTYH2 were constructed using pSicoR (Addgene, #11579) with GFP replaced by mCherry. shRNA sequences were as follows: LRRC8A: 5′-GGTACAACCACATCGCCTA-3′ [3]; TTYH1: 5′-GCATCGGTTTCTATGGCAACA-3′; TTYH2: 5′-GGATTATCTGGACGCTCTTGC-3′ [13]. A pSicoR construct containing a scrambled shRNA was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…While there are only two studies focused specifically on proteins that directly interact with individual Tweety proteins, there are several large-scale interactome studies that shed light on putative interacting partners. In terms of Tweety-focused studies, TTYH2 has also been shown through yeast two-hybrid assay to interact with β-COP, a subunit of Coat Protein Complex I, a protein required for transport from the ER to the Golgi (Ryu et al, 2019 ). This was further supported through Co-IP experiments.…”
Section: Structure and Biochemical Function Of Tweety Family Proteinsmentioning
confidence: 99%
“…This was further supported through Co-IP experiments. Additionally, β-COP was shown to play a role in trafficking TTYH2 to the plasma membrane as coexpression of TTYH2 and β-COP in COS-7 cells reduced TTYH2 expression at the cell surface, likely due to its role in both retrograde and anterograde transport (Ryu et al, 2019 ). Additionally, TTYH2 and TTYH3 expression was shown to be regulated through ubiquitination via Nedd4-2, a ubiquitin ligase in HEK293 cells (He et al, 2008a ).…”
Section: Structure and Biochemical Function Of Tweety Family Proteinsmentioning
confidence: 99%